Preparação e caracterização de membranas de celulose regenerada a partir da celulose extraída de resíduos agroindustriais para aplicação em processos de separação - Souza, Edmar Eustaquio de; Vale, Rayane da Silva; Vieira, Julia Graciele; Ribeiro, Sabrina Dias; Rodrigues Filho, Guimes; Marques, Fabiana Aparecida; Nascimento de Assuncao, Rosana Maria; Meireles, Carla da Silva; Barud, Hernane da Silva [UNESP] (Soc Brasileira Quimica, 2015)
The aim of this study was to produce membranes using the adapted cuprammonium method. The cellulose utilized was obtained from recycled agroindustrial residues: sugarcane bagasse, corn stover and soybean hulls. The levels of Cu (II) ions in regenerated cellulose membranes produced with cellulose from bagasse, corn stover and soybean hulls were 0.0236 wt%, 0.0255 wt% and 0.0268 wt%, respectively. These levels were approximately 15 times lower than those observed in previous studies (0.3634 wt%). Cellular viability data show that membranes produced from bagasse cellulose do not present toxicity to the cellular cultures studied. These results demonstrate an evolution in production of regenerated cellulose membranes from agroindustrial residues mainly due to a decrease in the Cu (II) ions level, showing the possibility of application of these systems with improved membranes processing.
Preparation and characterization of regenerated cellulose membranes using cellulose extracted from agroindustrial residues for application in separation processes
Keywords: Regenerated cellulose; Agroindustrial residues; Separation process; Membranes